Direct ageing response on the microstructure and mechanical properties of electron beam welds of Ni-Cr-Fe alloy used in vacuum insulated tubing. (June 2020) - Sujai, S.; Devendranath Ramkumar, K.
Graphical abstract: Highlights: Grain boundary precipitation behaviour studies on EB weld seams of Incoloy 925. Formation of sigma phase, M7 C3 and M23 C6 carbides in the grain boundaries of weld microstructures in both the conditions. Pensive discussion on the HAZ Liquation cracking. Improved joint strength and bend ductility of EB weld joints after subjected to direct ageing treatment. Abstract: Incoloy 925 joints of 5 mm thick were accomplished by adopting high energy density, electron beam welding (EBW) process. Although the weld seam microstructure was completely austenitic and free from solidification cracking, the heat-affected zone (HAZ) of EBW joints experienced liquation cracking. The mechanical behaviour of the EB weld seams in the as-welded and direct aged (DA) at 732 °C for 4 h and air-cooled conditions were compared. Electron backscattered X-ray diffraction (EBSD) analysis revealed the formation of strengthening precipitate γ′ in the matrix and the precipitation of sigma (σ) phase, M7 C3, M23 C6 and Ti-rich carbides formed along the crystallite boundaries in the DA condition. The tensile property outcomes opined that the joint efficiency of the weld seams in the DA condition (99.32 %) was found to be better than the ones in the as-welded condition (71.32 %). Also, the yield strength has been considerably improved in the EB weld seams subjected to DA conditions. The carbide precipitation along the grain boundaries is discontinuous and also not effective in pinning the dislocations under impact loads.